Supercapacitors Based on Carbon Nanotubes and Hybrid Polymer Electrolytes - Lawal Sa'adu
The importance of supercapacitors cannot be over emphasized, especially in this current era of search for an improved energy storage device that is mechanically flexible, more lightweight, and more compact for use in a significant number of applications; from wearable energy that could be incorporated into garments, to space applications where the cost by weight and volume is huge. Supercapacitors are very attractive for portable electronics as well as automotive applications due to their high specific power and durability. This research focuses on fabrication of supercapacitor cells using carbon nanotube as the main active electrode material and hybrid polymer electrolyte as the separator. 90 % of each of the following commercially prepared carbon nanotubes namely; Carboxyl, Hydroxyl and the Normal CNTs and 10 % of polyvinylidene fluoride (PVDF) and Poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) as a binder have been selected for the electrode film. On the other hand, two different types of aqueous polymer electrolytes - Pure Solid Polymer Electrolyte (PSPE) and Hybrid Solid Polymer Electrolytes (HSPE) (incorporated with cellulose filter paper) - were prepared from the solution of polyvinyl alcohol (PVA) and orthophosphoric acid (H3PO4) in different percentage ratios from 0 wt. % to 70 with. %. Conductivity studies conducted at room temperature shows that the electrolyte made from HSPE delivered the highest conductivity of 1.67 x 10-3. Scm-1 as against PSPE (2.56 x 10-3 Scm-1). Based on these results and having noticed the potentials the HSPE had over PSPE, Supercapacitors cells were fabricated from 50, 60 and 70 wt.% of phosphoric acid in PVA/H3PO4/cellulose blends (i.e. H50,H60 and H70). All the supercapacitors cells have been tested for their cyclic behaviors and galvanostatic charge-discharge (CD). Of the Nine succesfully fabricated cells (three from each sample of CNTs), C90H70 (i.e. Cell - C (C90PVdF-HFP10 |H70| C90PVdF-HFP10)) delivered the highest capacitance of 313 Fg-1 when calculated using cyclic voltammetry within the electrochemical voltage window of 0.0 - 1V. However, when measured by galvanostatic CD, its effective capacitance, energy and power densities obtained are 153 Fg-1, 76.50 Whg-1 and 1.00 Wg-1 respectively, and attained the overall columbic efficiency of 93.8 % with more than 5000 cycleability. Other important tests conducted on both samples of electrode and electrolytes are Thermogravimetric Analysis (TGA), Field Emmisison Scanning Electron Microscope (FESEM), X-Ray Diffraction (XRD).